Martha Cheung, In Memoriam (translation. a transdisciplinary journal, 2022)
On behalf o f translation's edi torial board I would l ike to express our deep sadness for the passing away of Martha Cheung. We will always remember her for her distinguished scholarship, her engagement for the "international turn" in translation studies, and her teaching. Her publications, among which the groundbreaking Anthology of Chinese Discourse on Translation (2006) are a milestone for students and scholars the world over.